Design and dynamic analysis of metal rubber isolators between satellite and carrier rocket system - X. Cao; C. Wei; J. Liang; L. Wang (Mechanical Sciences, 2019)
To achieve mobility and rapid-response, vehicles are used to launch satellites, and such systems will inevitably undergo random vibrations caused by uneven ground excitations. However, cameras or other high-precision satellite payloads cannot withstand such harsh mechanical environment in the absence of isolators. Hence, in the present paper, due to the advantages of the superior damping properties of metal rubber (MR), we designed MR structures to absorb vibrations. Correspondingly, the dynamical behaviours of the integrated system were comprehensively analysed to ensure that vibrations would not cause the payloads to collide with the fairing. In addition, the effects of geometric parameters of the isolated structures on the vibration properties of the system were investigated. This work provides a feasible design method of using simple MR structures, instead of very complicated isolators, for a mobile satellite launching system moving on rough roads.